Different views of the dynamic landscape covered by the 5'-hairpin of the 7SK small nuclear RNA - Brillet, Karl; Martinez-Zapien, Denise; Bec, Guillaume; Ennifar, Eric; Dock-Bregeon, Anne-Catherine; Lebars, Isabelle (RNA (Cambridge), 2020)
The 7SK small nuclear RNA (7SKsnRNA) plays a key role in the regulation of RNA polymerase II by sequestrating and inhibiting the positive transcription elongation factor b (P-TEFb) in the 7SK ribonucleoprotein complex (7SKsnRNP), a process mediated by interaction with the protein HEXIM. P-TEFb is also an essential cellular factor recruited by the viral protein Tat to ensure the replication of the viral RNA in the infection cycle of the human immunodeficiency virus (HIV-1). Tat promotes the release of P-TEFb from the 7SKsnRNP and subsequent activation of transcription, by displacing HEXIM from the 5'-hairpin of the 7SKsnRNA. This hairpin (HP1), comprising the signature sequence of the 7SKsnRNA, has been the subject of three independent structural studies aimed at identifying the structural features that could drive the recognition by the two proteins, both depending on arginine-rich motifs (ARM). Interestingly, four distinct structures were determined. In an attempt to provide a comprehensive view of the structure-function relationship of this versatile RNA, we present here a structural analysis of the models, highlighting how HP1 is able to adopt distinct conformations with significant impact on the compactness of the molecule. Since these models are solved under different conditions by nuclear magnetic resonance (NMR) and crystallography, the impact of the buffer composition on the conformational variation was investigated by complementary biophysical approaches. Finally, using isothermal titration calorimetry, we determined the thermodynamic signatures of the Tat-ARM and HEXIM-ARM peptide interactions with the RNA, showing that they are associated with distinct binding mechanisms.